Traceable measurements of He, Ne, Ar, Kr, and Xe photoionization cross sections in the EUV spectral range. (12th June 2018) - Schaefer, R; Gottwald, A; Richter, M
Abstract: The photoionization cross sections for atomic He, Ne, Ar, Kr and Xe were determined with a double ionization chamber using monochromatized synchrotron radiation from the electron storage ring Metrology Light Source in the wavelength range from 25 to 90 nm. Particular attention was paid to full traceability to the SI units, and thus to achieve reliably small measurement uncertainties, i.e. in the sub-percent range throughout most of the investigated spectral range. Thus, we basically substantiated already existing data, however now with pointwise (i.e. non-interpolated) data and reduced uncertainties. The data is of great benefit for rare gas photoionization-based radiometric standards in numerous applications, e.g. space-based ionization chamber measurements, gas monitor detectors for free electron lasers, or future SI traceable gas analytics.